The barrier functions of the cervical mucus plugs and purified mucins against a panel of HIV-1 strains in the contexts of cell-free and cell-to-cell infections - Mhlekude, Baxolele (Division of General Surgery, 2019)
HIV must traverse the mucosal barriers in order to establish a clinical infection during sexual transmission in the female reproductive tract. The cervical tract of a pregnant woman produces a mucin-rich solid material called the cervical mucus plug, which prevents the entry of bacteria and other foreign substances from the vaginal tract into the uterus. Our laboratory found that the cervical mucins—but not the crude cervical mucus plugs—isolated and purified from the mucus plugs inhibit HIV-1 infection in an in vitro cell-free inhibition assay. We aimed to characterize and compare the inhibition of cell-free and cell-associated HIV-1 strains by the crude cervical mucus plugs and purified cervical mucins. Fifty-two cervical mucus plugs were collected from women in labour in 6 M guanidine hydrochloride with protease inhibitors. The cervical mucus plugs were solubilised in 6 M guanidine hydrochloride with protease inhibitors, centrifuged, dialysed against distilled water and lyophilized. The mucins were purified by caesium chloride density gradient ultracentrifugation and size exclusion chromatography, dialysed against distilled water and lyophilized. The lyophilized samples were reconstituted in cell culture medium and used in cell viability assays, after which they were probed against a panel of replication-competent strains of HIV-1 using functional assays. The crude cervical mucus plugs inhibited cell-free HIV-1 strains more potently than the purified mucins. Depending on the infecting HIV-1 strain, this potency varied between and within samples from different donors. The data from a FACS-based virus fusion assay showed that some crude cervical mucus plugs inhibit fusion between the virus and target cell. Interestingly, cell-to-cell transmission of HIV-1 partially overcame the anti-viral activity of the crude cervical mucus plugs. Furthermore, despite the donor’s HIV status, the biochemical analysis of the purified cervical mucins showed comparable characteristics in terms of buoyancy in caesium chloride and guanidine hydrochloride, glycoprotein and protein contents, which were recapitulated in the HIV inhibition assays. In conclusion, the crude cervical mucus plugs can potently inhibit different strains of HIV-1 compared to the purified cervical mucins, and this potency is more pronounced in the HIV positive cohort compared to the HIV negative cohort.